Knowledge, attitude and practice in prevention of foot ulcer among diabetes mellitus patients in a public health clinic, Selangor, Malaysia - Mohd Awwad, Khalaf Abdelfattah (2019)
Introduction: Globally, diabetes has risen from 108 million in 1980 to 422 million in 2014. In comparison to ten other regional countries in Asia, Malaysia had the highest number of cases of diabetes and raised blood sugar levels, which can lead to foot ulcer complications. The knowledge, attitude, and practice of diabetic foot management are important factors in the management of diabetic patients. Objective: The objective of the study was to assess the knowledge, attitude, and practice of diabetic patients regarding the prevention of foot ulcers in Klinik Kesihatan Seri Kembangan. Method: A cross-sectional study was conducted among 483 diabetic patients at Klinik Kesihatan Seri Kembangan. The data were collected using a pre-tested selfadministrated structured questionnaire. The study analysis was done using Statistical Package for Social Sciences (SPSS) version 24 software. Descriptive statistics, the Chi-square test, and Logistic regression were used in this study. All tests were estimated to be two-sided and the statistical significance was considered to be at p< 0.05. Results: A total of 483 diabetic patients participated in this study of which 279 (57.8%) were female and 204 (42.2%) were male. The majority (237 or 49.1%) of the respondents had secondary school education and 298 (61.7%) were married. The majority of the respondents had satisfactory knowledge (68.7%) and practice (57.8%) whereas the attitude was unfavourable (61.7%). There were 150 respondents with favourable attitude who had good knowledge, while 198 respondents with unfavourable attitude had good knowledge; this finding showed a significant association between knowledge and attitude. The predictors were statistically significantly associated with knowledge, attitude, and practice. Conclusion: The study concluded that the levels of the participants were satisfactory for knowledge, unfavourable for attitude, and satisfactory for practice. There was also a significant association between knowledge and attitude regarding the prevention of foot ulcers. It also indicated that socio-demographics were associated with knowledge, attitude, and practice in respect of the prevention of foot ulcers.